Asas Keterbukaan dalam Pelaksanaan Fungsi Legislasi Dewan Perwakilan Rakyat (Perspektif Islam dan Hukum Positif di Indonesia) - Sirajul Munir (Program Studi Hukum Keluarga Islam, 2021)
Laws have binding power and coercion after being passed in the legislative process. Therefore, the legislative process is bound by several principles, one of which is the principle of openness. Openness is the principle of governance that is based on participation. This article aims to explain the principle of openness in the implementation of the legislative function of the House of Representatives (DPR) in terms of Islamic Law and Positive Law in Indonesia. The type of method used in writing this article is normative juridical using a qualitative approach based on the statute approach and the conceptual approach. Sources of data are used in the form of secondary data which includes primary legal materials, secondary legal materials, and tertiary legal materials. For data analysis, this article uses a qualitative descriptive data analysis technique. The results of the study indicate that the principle of openness in the implementation of the legislative function of the DPR was formed to accommodate public participation so that the legislative product does not harm the community. In Islam, several arguments can be used as a normative basis for comparing shura and the principle of openness in the implementation of the legislative functions of the DPR. The principle of openness has the same meaning as Shura in the legislative process, namely public involvement. Shura in Islamic teachings provides a moral foundation when the DPR carries out its legislative function in a democratic system.Undang-undang memiliki daya ikat dan daya paksa setelah disahkan dalam proses legislasi. Oleh sebab itu, proses legislasi terikat pada beberapa asas, salahsatunyaadalahasasketerbukaan.Keterbukaanmerupakanasaspenyelenggaraanpemerintahan yang bertumpupadapartisipasi.Tulisan artikel ini bertujuan untuk menjelaskan tentang asas keterbukaan dalam pelaksanaan fungsi legislasi Dewan Perwakilan Rakyat (DPR) ditinjau dari Hukum Islam dan Hukum Positif di Indonesia.Jenis metode yang digunakan dalam penulisan artikel ini adalah yuridis normatif dengan menggunakan basis pendekatan kualitatif yakni statute approach dan conceptual approach. Sumber data yang digunakan berupa data sekunder yang meliputi bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Untuk analisis data, artikel ini menggunakan teknik analisis data berupa deskriptif kualitatif. Hasil penelitian menunjukkan bahwa asas keterbukaan dalam pelaksanaan fungsi legislasi DPR dibentuk untuk mengakomodir partisipasi publik sehingga produk legislasi tidak merugikan masyarakat. Dalam Islam, ada beberapa dalil yang dapat dijadikan landasan normatif untuk membandingkan antara syura dan asas keterbukaan dalam pelaksanaan fungsi legislasi DPR. Asas keterbukaan memiliki makna sama dengan Syura dalam proses legislasi yakni keterlibatan publik. Syura dalam ajaran Islam memberikan landasan moral ketika DPR melaksanakan fungsi legislasinya dalam sistem demokrasi.